2020
DOI: 10.1017/s0033291720003852
|View full text |Cite
|
Sign up to set email alerts
|

The prediction of resilience to alcohol consumption in youths: insular and subcallosal cingulate myeloarchitecture

Abstract: Background The prediction of alcohol consumption in youths and particularly biomarkers of resilience, is critical for early intervention to reduce the risk of subsequent harmful alcohol use. Methods At baseline, the longitudinal relaxation rate (R1), indexing grey matter myelination (i.e. myeloarchitecture), was assessed in 86 adolescents/young adults (mean age = 21.76, range: 15.75–26.67 years). The Alcohol Use Disorder Identification Test (AUDIT) was assessed at baseline, 1- and 2-year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 87 publications
0
2
0
Order By: Relevance
“…Weidacker et al concluded that grey matter myelinations (myeloarchitecture) could be a potential protective biomarker, as greater baseline myeloarchitecture predicted a lower risk for harmful alcohol use at two-year follow-up. (87)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Weidacker et al concluded that grey matter myelinations (myeloarchitecture) could be a potential protective biomarker, as greater baseline myeloarchitecture predicted a lower risk for harmful alcohol use at two-year follow-up. (87)…”
Section: Resultsmentioning
confidence: 99%
“…Weidacker et al concluded that grey matter myelinations (myeloarchitecture) could be a potential protective biomarker, as greater baseline myeloarchitecture predicted a lower risk for harmful alcohol use at two-year follow-up. (87) Impulsivity is another aspect of interest for AUD prediction in adolescents. Sex-dependent differential trajectories of impulsivity in high school students may increase an individual's susceptibility to substance use disorder, including alcohol.…”
Section: Aud In Adolescentsmentioning
confidence: 99%
“…Alcoholism & Drug Addiction / Alkoholizm i narkomania 2023; 36, 2 Neurobiologia regulacji emocji w AUD i innych modelach picia W badaniach neuroobrazowych mózgu oceniających spożycie alkoholu wśród młodzieży zaobserwowano, że wyspa jest istotnie zaangażowana w kodowanie funkcji autonomicznych związanych z subiektywnymi stanami głodu alkoholowego i ryzykownymi procesami decyzyjnymi, a podspoidłowy zakręt obręczy leży u podstaw regulacji emocji [71]. Inne prace sugerują, że mniejsze zaangażowanie dużych obwodów mózgowych wspierających odgórną kontrolę uwagi, szczególnie podczas doświadczania negatywnych emocji, wiąże się z bardziej problemowym piciem u młodych dorosłych [72].…”
Section: Emotion Regulation Strategies In Populations Of Problem Drin...unclassified
“…obserwowano, że alkohol zakłóca łączność między regionami przedniej części wyspy (anterior insula -aINS) a grzbietową przednią korą zakrętu obręczy (dorsal anterior cingulate cortex -dACC), co upośledza wykrycie i ocenę emocjonalnie istotnych informacji, a tym samym wzmacnia bezpośrednie anksjolityczne efekty alkoholu [75]. Wyniki badań sugerują, że w niektórych deficytach poznawczych i afektywnych obserwowanych u osób z AUD może pośredniczyć, The neurobiology of emotion regulation in AUD and other models of drinking Brain neuroimaging studies assessing alcohol use among adolescents have observed that the insula is significantly involved in encoding autonomic functions related to subjective states of alcohol craving and risky decision-making and that the sublimbic cingulate rim lies at the heart of emotion regulation [71]. Other work suggests that the smaller involvement of large brain circuits supporting top-down attentional control, particularly during the experience of negative emotions, is associated with more problem drinking in young adults [72].…”
Section: Emotion Regulation Strategies In Populations Of Problem Drin...unclassified